SPECTROSCOPIC INVESTIGATIONS OF GALACTIC CLUSTERS WITH ASSOCIATED CEPHEID VARIABLES. I. POLARIS CLUSTER AND α UMI - Usenko, I. A.; Miroshnichenko, A. S.; Danford, S.; Kovtyukh, V. V.; Turner, D. G.; Shulga, A. V.; Protsyuk, Yu. I. (Одеські астрономічні публікації, 2018)
We present the results of an analysis of the spectra of nine so called Polaris cluster A−FV stars obtained during 2016 - 2018. Radial velocities (RV) and GAIA DR 18 parallaxes-distances for these stars allow us to determine their membership in the cluster and to construct its 3D kinematic model. However Teﬀ for four stars determined spectroscopically give cause for doubts about the GAIA DR 18 parallaxes accuracy. The comparison between their MV and distances with the those from Pecaut & Mamajek (2013) calibrations shows signiﬁcant diﬀerences for the objects with parallaxes less than 8 mas. The diﬀerences in distances increase exponentially with decreasing parallax. These facts indicate an unreliability of the GAIA DR2 parallx measurements of less than 10 mas. We estimated the distance to Polaris B to be 104.2 pc.